Dynamic Spirals of Nanoparticles in Light‐Responsive Polygonal Fields. Issue 39 (6th August 2019) - Orlova, Tetiana; Plamont, Rémi; Depauw, Alexis; Katsonis, Nathalie
Abstract: Nanoparticles tend to aggregate once integrated into soft matter and consequently, self‐assembling nanoparticles into large‐scale, regular, well‐defined, and ultimately chiral patterns remains an ongoing challenge toward the design and realization of organized superstructures of nanoparticles. The patterns of nanoparticles that are reported in liquid crystals so far are all static, and this lack of responsiveness extends to assemblies of nanoparticles formed in topological singularities and other localized structures of anisotropic matter. Here, it is shown that gold nanoparticles form spiral superstructures in polygonal fields of cholesteric liquid crystals. Moreover, when the cholesteric liquid crystals incorporate molecular photoswitches in their composition, the pitch of the nanoparticulate spirals follows the light‐induced reorganization of the cholesteric liquid crystals. These experimental findings indicate that chiral liquid crystals can be used as chiral and dynamic templates for soft photonic nanomaterials. Controlling the geometry of these spirals of nanoparticles will ultimately allow modulating the plasmonic signature of hybrid and chiral systems. Abstract : The long‐range organization of nanoparticles is templated effectively by double spirals that lie on the convex cones of polygonal fields of chiral liquid crystals. Moreover, the distance between the spiral arms of nanoparticles can be controlled by light. This approach toward dynamic, long‐range, and self‐assembled patterns of metallic nanoparticles features chiral amplification across length scales and holds perspective for advanced hybrid nanomaterials.